THE USE OF DATA SCIENCE MODELS TO ANALYZE THE DEVELOPMENT STATE OF THE EU AND UKRAINE IT SECTOR - CHAGOVETS, LIUBOV; PROKOPOVYCH, SVITLANA; PANASENKO, OKSANA; CHAHOVETS, VITA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper is devoted to the assessment of the development state of the EU and Ukraine’s IT sector. For the countries of the EU, the IT market is a priority direction and a strategic goal of the development of the digital economy. Ukraine is also trying to introduce the use of digital technologies in all areas of activity. The purpose of the study is to develop economic and mathematical models for assessing and analyzing the level of development of the IT sector in the EU and Ukraine, which allow for the analysis of the strengths and weaknesses of this sector, to form recommendations. The analysis of the features of the IT sector development was carried out and key indicators were selected. A set of models for assessing the level of development of the IT sector of the economy in the EU has been developed. Classification models of EU countries by the level of development of the IT sector were built using cluster analysis methods. The analysis of the digital development state of Ukraine on the European market was carried out using discriminant analysis. The regression model for forecasting the level of development of the IT sphere in Ukraine has been developed. The results of the research can be used during the implementation of global and regional programs for the development of the IT sector in the EU countries and Ukraine.